Analisis Pengaruh Musim Penghujan Dan Musim Kemarau Terhadap Kualitas Wilayah Sungai Brantas - Vikhory Bagus Wahyu Nugroho; Juan Vincent Elfonda; Tuhu Agung Rachmanto (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
The Brantas River is a large river in East Java that has an important role for the community. Seasonal changes have an impact on the quality of the Brantas River in Indonesia. Testing is conducted by comparing samples taken twice a year, representing the dry and rainy seasons. The river's quality is analyzed based on several parameters such as Dissolved Oxygen (DO), BOD, COD, NO3-N, and Phosphate. The results are then compared with the standard river quality according to Government Regulation No. 22 of 2021. The analysis results indicate that the season has a significant impact on the river water quality, as seen from the different parameters in each season.